Resourceful Civil Society Navigating the Changing Landscapes of Civil Society Organizations - Kravchenko, Zhanna; Kings, Lisa; Jezierska, Katarzyna (Palgrave Studies in Third Sector Research, 2022)
This open access book examines how civil society organizations in Poland, Russia, and Sweden (re)act to transformations of opportunities and limitations in access to various forms of resources. The volume's contributions discuss the constraints associated with different types of resources as well as organizations' capacities to generate resources-or compensate for their lack-as they negotiate and contest barriers. The resourcefulness of civil society is revealed to be rooted in a variety of capabilities: converting resources, eliciting organizational change, and metamorphosing in response to organizational and environmental development. ​